SPHAGNUM ANTISETTICO : TOPICAL ANTISEPTIC FROM SPHAGNUM MOSS WITH AN BEGONIA EXTRACT FOR WOUND CARE - Pratama, Jasmine Namira; Raissa, Janitra Putri; Purbadi, Maharani Bela Putri; Siswara, Jhihan Mauliddhiya; Destiany, Vany; Taufik, Agung (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
Sphagnum moss a type of moss commonly found in moist environments, typically in tropical regions. Peat contains both solid and liquid fractions and was used in treating skin conditions due to its antiseptic properties. It was added to ointments and medicinal soaps until the late 1960s (Jacek Drobnik, Adam Stebel, 2017). Similarly, the Begonia multangula plant, which has been extensively studied, has shown antibacterial properties that can be used as an antiseptic for wound care. To find an alternative antiseptic that is easy to use, we tested these two plants, which have been researched for their beneficial properties in treating and healing wounds.